The Directness Levels of Criticism: A Cross-Cultural Comparative Study of Korean and American Youtuber - Aan Anisah Agustini Safari (Script Journal: Journal of Linguistics and English Teaching, 2020)
Background: Different countries may have different cultures that are influenced by their religion, traditions, or norms. These differences affect the way they speak, such as when they are commenting or giving opinions. Due to the way people express speech acts can be varied and lead to misinterpretation because of their differences, the researcher was intrigued to conduct this study. Methodology: This cross-cultural study was carried out to observe and compare the speech act of criticism between Korean and American YouTubers and to investigate the role of their cultural background in influencing the directness level they conveyed. First, the researcher selected three Korean Youtubers and Americans as well with food review content. Second, the researcher watched one video from each channel and took notes on every expression of criticism they used. Findings: The result of this study demonstrates that in American YouTubers speech, direct strategy emerges more frequently than the indirect one. Conversely, Korean YouTubers tend to use the indirect one. The finding also indicates that their speech behavior is related to their cultural norms, in which American culture encourages clear personal opinions, while Korean culture is a restraint to express their opinion or feeling clearly. Conclusion: Due to the considerable difference between Korean and American YouTuber speech, it can be concluded that culture takes a significant part in shaping one’s speech behavior. That is why people with different cultural backgrounds may have different ways of speaking. Keywords: Criticism; cross-culture pragmatic; directness-indirectness.